2018–2019 Florida Citrus Production Guide: Rust Mites, Spider Mites, and Other Phytophagous Mites - Michael E. Rogers; Philip A. Stansly; Jawwad A. Qureshi (EDIS, 2019)
This 6-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. Written by M. E. Rogers, P. A. Stansly, and J. A. Qureshi, and published by the Entomology and Nematology Department, January 2019.